Flexural Capacity and Behavior of RC Hollow Bridge Beams after a Time Service of 24 Years. (21st July 2020) - Qu, Guangzhen; Zhou, Guangli; Lv, Sizhong; Huang, Pingming
Abstract : The residual bearing capacity of existing bridges has been a controversial topic for engineers and technicians. In order to accurately evaluate the actual bearing capacity of a 24-year-old RC hollow beam bridge, its components with different thickness concrete leveling layer were removed and transported back to the laboratory. The representative static and dynamic responses of the two beams were monitored during the whole procedure. A quick assessment of loading capacity of bridge using crack height and a parameter correction method for the crack width prediction formula in the code were proposed. In addition, comparison of measured and current design codes GB 50010 and ACI 318 predicted behaviour of existing beams was also presented. The results showed that the bending process of the RC hollow beam went through the elastic phase to the elastic-plastic phase and to the final failure. The actual flexural capacity of two beams was 10% larger than the calculated values. The natural vibration frequencies of the beam changed slightly before plastic stage, but the modal amplitude increased with the increase of degree of damage, once the beam entered plastic stage. The predicted deflections according to GB50010 were consistent with the experimental values at about 200 kN; for the code ACI, as the loading force increased, the difference between the two gradually decreased.